Bionic beasts : saving animal lives with artificial flippers, legs, and beaks (Millbrook Press, 2021)
"Using innovative designs and technology such as 3-D printing, humans are helping animals in need. Discover the amazing true stories of five animals that have survived thanks to their prosthetic body parts"--